Wiley Encyclopedia of Electrical and Electronics Engineering 1999
DOI: 10.1002/047134608x.w7006
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Doping

Abstract: The sections in this article are Formalism of Diffusion Realization of the Diffusion Processes Atomic Models of Diffusion Diffusion of Impurities The Role of Oxidation and Nitridation During Diffusion The Role of Substrate Orientation in Diffusion Diffusion in Polycrystalline and Amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…4 Owing to its remarkable properties, HfB 2 has potential applications in microelectronics: it performs well as a diffusion barrier between copper and silicon 5 and it has been investigated as a contact metal and a gate electrode material for Si metal-oxide-semiconductor fieldeffect transistors. 6,7 In 1988, two groups independently discovered a highly attractive chemical vapor deposition route to HfB 2 thin films from the single-source precursor Hf͑BH 4 ͒ 4 . 8,9 We have recently shown that the kinetics of this chemical vapor deposition ͑CVD͒ process exhibits Langmuirian behavior, i.e., the reaction rate saturates at high precursor pressure.…”
Section: Introductionmentioning
confidence: 99%
“…4 Owing to its remarkable properties, HfB 2 has potential applications in microelectronics: it performs well as a diffusion barrier between copper and silicon 5 and it has been investigated as a contact metal and a gate electrode material for Si metal-oxide-semiconductor fieldeffect transistors. 6,7 In 1988, two groups independently discovered a highly attractive chemical vapor deposition route to HfB 2 thin films from the single-source precursor Hf͑BH 4 ͒ 4 . 8,9 We have recently shown that the kinetics of this chemical vapor deposition ͑CVD͒ process exhibits Langmuirian behavior, i.e., the reaction rate saturates at high precursor pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal diborides are attractive candidates for many engineering applications owing to their attractive properties which include high melting temperature, high hardness and low electrical resistivity [1][2][3][4][5][6]. Zirconium diboride has been proposed as a substrate for the epitaxial overgrowth of GaN because the lattice constant and thermal expansion coefficient of ZrB 2 (0 0 0 1) match reasonably well with those of GaN(0 0 0 1) [7,8].…”
Section: Introductionmentioning
confidence: 99%